Proposal for a substitution program for imported wheat based on the development of the Andean agricultural economy - Tantaleán Arbulú, Javier (1984)
In 1979, the Cartagena Agreement Commission approved decision 126, by virtue of which the Andean Technological Development Projects in the Food Area (PADT/Food) were put into effect, whose main objectives were to promote agricultural production and industrial food that allow an increase in the nutritional level of the population, and a better and greater use of existing national resources.